Requirements of the cytosolic iron–sulfur cluster assembly pathway in Arabidopsis - Bernard, Delphine G. (The Royal Society, 2013)
The assembly of iron–sulfur (Fe–S) clusters requires dedicated protein factors inside the living cell. Striking similarities between prokaryotic and eukaryotic assembly proteins suggest that plant cells inherited two different pathways through endosymbiosis: the ISC pathway in mitochondria and the SUF pathway in plastids. Fe–S proteins are also found in the cytosol and nucleus, but little is known about how they are assembled in plant cells. Here, we show that neither plastid assembly proteins nor the cytosolic cysteine desulfurase ABA3 are required for the activity of cytosolic aconitase, which depends on a [4Fe–4S] cluster. In contrast, cytosolic aconitase activity depended on the mitochondrial cysteine desulfurase NFS1 and the mitochondrial transporter ATM3. In addition, we were able to complement a yeast mutant in the cytosolic Fe–S cluster assembly pathway, dre2, with the Arabidopsis homologue AtDRE2, but only when expressed together with the diflavin reductase AtTAH18. Spectroscopic characterization showed that purified AtDRE2 could bind up to two Fe–S clusters. Purified AtTAH18 bound one flavin per molecule and was able to accept electrons from NAD(P)H. These results suggest that the proteins involved in cytosolic Fe–S cluster assembly are highly conserved, and that dependence on the mitochondria arose before the second endosymbiosis event leading to plastids.